ASSESSING NURSES COMPETENCE IN CHEST TUBE MANAGEMENT: AN ICU-BASED STUDY IN TERTIARY CARE PUBLIC SECTOR HOSPITAL KARACHI, PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Objectives: Chest tubes serve a vital function in regulating intra-Pleural pressure and averting severe complications, including pulmonary collapse. The responsibility for their effective management predominantly rests with nurses who provide care to patients undergoing this intervention. Therefore, this study was undertaken to assessing nurse’s competence in chest tube management at intensive care units in tertiary care public sector hospital Karachi, Pakistan.Methodology: This descriptive cross-sectional study employed a convenience sampling technique, recruiting a total of 120 participants. Data were collected using a structured questionnaire that included demographic information, followed by an 18-item tool designed to evaluate nurses’ competence in chest tube management. The level of competence was determined by calculating the percentage of correct responses to the 18 competence-based items. Results: Out of the 120 nurses surveyed, 59.2% (n=71) were male, while 55% (n=66) were below the age of 36 years. In terms of professional experience, 66.7% (n=80) had worked for up to 10 years. Only 20% (n=24) reported attending training sessions related to thoracic diseases. The mean competence score was 57.3 ± 17.2. Based on the scoring criteria, 30% (n=36) of participants demonstrated low competence (80%).Conclusion: The findings of this study indicated that critical care nurses at the tertiary care public sector intensive care nurses possessed a moderate level of competence regarding chest tube management. These results highlight the necessity of implementing structured and comprehensive training initiatives specifically tailored to chest tube care. Such educational interventions are essential for strengthening nurses’ proficiency and ensuring the delivery of safe and effective patient care in critical settings.